2001
DOI: 10.1016/s0896-6273(01)00520-7
|View full text |Cite
|
Sign up to set email alerts
|

Heteromeric AMPA Receptors Assemble with a Preferred Subunit Stoichiometry and Spatial Arrangement

Abstract: AMPA receptors are thought to be a tetrameric assembly of the subunits GluR1-4. We have examined whether two coexpressed subunits (GluR1/2) combine at random to form channels, or preferentially assemble with a specific stoichiometry and spatial configuration. The subunits carried markers controlling ion permeation and desensitization, and these properties were monitored as a function of relative expression level and subunit composition. Homomeric receptors assembled stochastically while heteromeric receptors p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
190
2
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(206 citation statements)
references
References 38 publications
12
190
2
2
Order By: Relevance
“…For both wild-type and T686A channels, most openings were to the two smallest open levels, although all our results were obtained at agonist concentrations at which the channels should often be fully occupied. Similar results were obtained before for GluR4 channels (Tomita et al, 2005), and results for GluR2-Q channels and native channels in hippocampal neurons are also consistent with a predominance of openings to small conductance states at high glutamate concentrations (Mansour et al, 2001;Gebhardt and Cull-Candy, 2006).…”
Section: Analysis Of Single-channel Currentssupporting
confidence: 89%
“…For both wild-type and T686A channels, most openings were to the two smallest open levels, although all our results were obtained at agonist concentrations at which the channels should often be fully occupied. Similar results were obtained before for GluR4 channels (Tomita et al, 2005), and results for GluR2-Q channels and native channels in hippocampal neurons are also consistent with a predominance of openings to small conductance states at high glutamate concentrations (Mansour et al, 2001;Gebhardt and Cull-Candy, 2006).…”
Section: Analysis Of Single-channel Currentssupporting
confidence: 89%
“…Assembly-Several studies have suggested a role for the X domain in the assembly of multimeric channels (10,12,32,33). Furthermore, experiments performed with separately expressed extracellular domains of GluR-D subunit indicate that the X domain is able to form dimers, consistent with a role in the assembly (11).…”
Section: Discussionmentioning
confidence: 87%
“…It should be noted, however, that most native AMPA receptors are heteromeric assemblies, and while the assembly of homomeric GluR-D channels seems to occur apparently normally in the absence of the X domain, the assembly of heteromeric subunit combinations may well require participation of the N-terminal region. Interestingly, a recent elegant study provided evidence that the assembly of homomeric AMPA receptors is a stochastic process, whereas heteromeric channels assemble with a preferred subunit stoichiometry (33). Considering the highly conserved ligand-binding domain and transmembrane segments of AMPA receptor subunits, it will be of considerable interest to test whether the more variable N-terminal domain (see below) would be able to guide the preferential formation of subunit pairs in the heteromeric assembly process.…”
Section: Discussionmentioning
confidence: 99%
“…Both AMPA 254 and NMDA receptors 255 are probably largely formed from tetrameric, heteromeric assemblies of different subunits 256 . Changes in these receptors are probably mediated through nuclear transcription factors 257 .…”
Section: The Iglur Family Is Classified Into Three Major Subtypes a Cmentioning
confidence: 99%